Pengaruh Strategi Emotion-Focused Coping Terhadap Pengelolaan Stres Akademik Mahasiswa Penyusun Skripsi IAIN Bukittinggi - Monalisa, Uhki; Santosa, Budi (Indonesian Research Journal on Education, 2022)
This research was carried out based on the phenomena that existed at IAIN Bukittinggi whichshowed that undergraduate thesis writing students were less able to manage academic stress in the thesis completion process. To increase changes in the management of student academic stress, a service in guidance and counseling was implemented, namely group counseling with emotionfocused coping strategies. The purpose of this study was to determine the effect of emotion-focusedcoping strategies on the management of academic stress in undergraduate thesis writing students. This research is a pre-experimental quantitative research with one group pretest and posttest research design. The research sample as many as 15 people, with purposive sampling technique, sampling based on consideration of the level of stress experienced by students. The technique in collecting data in this study is a questionnaire with a Likert scale measurement. The results showed that the highest percentage obtained after the administration of the EFC Strategy was 73% which was in the highest category, namely the 146-200 interval. The results of the hypothesis test of the Wilcoxon test value are known to have a significance of 0.001 0.05. This means that Ha is accepted stating that there is a significant effect of group counseling with emotion-focused coping strategies on the management of academic stress of thesis writing students at IAIN Bukittinggi.